Preparation method and application of silver-ammonia ion functionalized chitosan complex modified electrode based on carbon nanotube skeleton
Polyacrylic acid coats multi-walled carbon nanotubes and binds them to sulfonated chitosan and silver ammonia ions to form a PAA-MWCNTs-Ag-SCS complex, modifying the electrode surface, solving the problem of structural damage and low chiral surface sensitivity of multi-walled carbon nanotubes after acidification treatment, achieving high stability and efficient identification of phenylglycamine enantiomers.
Patent Information
- Application Number
- CN202211257923.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-13
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-10-13
AI Technical Summary
In the prior art, the structure of multi-walled carbon nanotubes is damaged after acidification, the conductivity is affected, and the sensitivity of the chiral surface is low, making it difficult to effectively identify the phenylglycamine enantiomer.
Multi-walled carbon nanotubes are coated with polyacrylic acid and combined with sulfonated chitosan and silver ammonia ions to form a PAA-MWCNTs-Ag-SCS complex, modifying the electrode surface and improving its dispersion, conductivity and structural stability.
High stability, sensitivity and ability of the electrode to efficiently identify phenylglycamine enantiomers are achieved, providing an efficient chiral sensing platform.
Smart Images

Figure CN115656280B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of analytical chemistry, and particularly relates to a preparation method and application of a silver-ammonia ion functionalized chitosan complex modified electrode based on a carbon nanotube skeleton. Background Art
[0002] As we all know, living things have chirality, and chiral compounds will show differences in physical and chemical properties in a chiral environment. Therefore, one of the two enantiomers of a chiral drug often has a good clinical effect, while the other has no effect or even has strong toxic side effects, which makes chiral recognition of great significance. The electrochemical method, which stands out with its advantages such as strong stability, high sensitivity, high detection efficiency and low cost, has gradually become the best choice for chiral recognition. The key to this method is to build an electrochemical sensing platform.
[0003] Multi-walled carbon nanotubes (MWCNTs) have both the inherent properties of carbon materials and the electrical and thermal conductivity of metal materials. They are often used to prepare chiral materials. For example, the preparation and application of multi-walled carbon nanotube-N-carboxymethyl chitosan chiral materials disclosed in Chinese patent document (application number 201810049533.7) acidifies the multi-walled carbon nanotubes to give them carboxyl groups so as to form amide bonds with the amino groups of ethylenediamine, and then uses the remaining amino groups of ethylenediamine to form amide bonds with the carboxyl groups of N-carboxymethyl chitosan. However, after the multi-walled carbon nanotubes are acidified, part of their structure is destroyed, the conductivity is affected, and the signal intensity of CV is significantly low. Another example is the carbon nanotube-pyrenetetracarboxylic acid-chitosan chiral material, preparation method and application disclosed in the Chinese patent document (application number 202111232106.0). It directly mixes and modifies carbon nanotubes with 3,4,9,10-pyrenetetracarboxylic acid in an ethanol solution to obtain carbon nanotubes / pyrenetetracarboxylic acid, and then modifies the glassy carbon electrode based on this material for tryptophan chiral recognition. However, the sensitivity of the chiral surface obtained by this patent is low, and the DPV peak current is about 30μA. Summary of the invention
[0004] The purpose of the present invention is to provide a silver-ammonia ion functionalized chitosan complex modified electrode based on a carbon nanotube skeleton and its application. Multi-walled carbon nanotubes have been widely studied due to their advantages such as small size, high specific surface area and high conductivity, and the PAA-MWCNTs of the present invention effectively solve the limitations of multi-walled carbon nanotubes on their application due to their poor dispersibility and easy agglomeration. The prepared sulfonated chitosan not only greatly increases the water solubility and optical activity of chitosan, but also fixes it to the surface of functionalized multi-walled carbon nanotubes through the electrostatic interaction between it and silver ammonium ions and PAA-MWCNTs, greatly increasing the rigidity and stability of its structure. The prepared PAA-MWCNTs-Ag-SCS complex modified electrode not only has strong stability, high reproducibility and sensitivity, low detection limit, but also has good recognition effect on phthalic anhydride amide enantiomers.
[0005] A silver-ammonia ion functionalized chitosan complex modified electrode based on a carbon nanotube skeleton, comprising a glassy carbon electrode and a PAA-MWCNTs-Ag-SCS complex modified on the surface of the glassy carbon electrode, wherein the PAA-MWCNTs-Ag-SCS complex comprises a polyacrylic acid coated carbon nanotube unit (PAA-MWCNTs) and a sulfonated chitosan unit (SCS), wherein the polyacrylic acid coated carbon nanotube unit and the sulfonated chitosan unit are connected by diammine silver ions;
[0006] The mass ratio of the carbon nanotube unit coated with polyacrylic acid to the sulfonated chitosan unit is 1:3-3:1.
[0007] Further, PAA-MWCNTs were prepared by weighing multi-walled carbon nanotubes (MWCNTs) and acrylic acid and dispersing them into 100 ml of acetone by ultrasonication, and then adding 2,2′-azoisobutyronitrile to initiate polymerization. The reaction was maintained at 60°C for 12 hours, and then the black solid product (PAA-MWCNTs) was filtered, washed with acetone and deionized water, and dried in a vacuum drying oven at 70°C to obtain PAA-MWCNTs solid powder.
[0008] The present invention uses polyacrylic acid (PAA) chains to encapsulate the surface of multi-walled carbon nanotubes, which not only avoids the defects of traditional acidification methods that destroy the structure of multi-walled carbon nanotubes and weaken their conductivity, but also increases the dispersibility of multi-walled carbon nanotubes and the ion transmission behavior on the surface, thereby increasing their conductivity.
[0009] Further, preparation of SCS: chitosan (CS) was completely dissolved in 80 ml of acetic acid aqueous solution, and then 1,3-propane sultone salt was dropped into the CS solution under nitrogen atmosphere, stirred at 60 °C for 6 h, and then the solute was poured into cold acetone and stirred vigorously to precipitate a white product, which was completely washed with methanol to remove unreacted 1,3-propane sultone, and the solid was dried in an oven for 12 h to obtain white powder SCS.
[0010] Further, the preparation of PAA-MWCNTs-Ag-SCS composite includes taking Ag 2 O solid was dissolved in 3 ml of 12.5% ammonia water, SCS was added and then ultrasonicated for 1 h, and then PAA-MWCNTs was added to obtain a PAA-MWCNTs-Ag-SCS suspension.
[0011] While the water solubility of sulfonated chitosan (SCS) is enhanced, the introduction of highly active sulfonated groups can combine with other compounds to change the spatial distribution of chitosan, thereby improving the chiral recognition effect of chitosan. In the present invention, after diamine silver ions combine with PAA-MWCNTs through electrostatic action in an alkaline environment, their positively charged surface combines with negatively charged sulfonated chitosan, so that sulfonated chitosan is loaded on the surface of PAA-MWCNTs-Ag to form a rod-shaped chiral surface material with stable structure, which not only shows extremely strong stability and excellent conductivity in the chiral recognition process, but also has good chiral recognition effect. This provides a new idea for building a chiral sensing platform with high stability and high sensitivity.
[0012] Furthermore, the preparation of the PAA-MWCNTs-Ag-SCS complex modified electrode includes: applying a PAA-MWCNTs-Ag-SCS suspension dropwise on the electrode surface, and drying under an infrared lamp to obtain a PAA-MWCNTs-Ag-SCS complex modified electrode.
[0013] The silver-ammonia ion functionalized chitosan complex modified electrode based on carbon nanotube skeleton is used for electrochemical identification of benzylglycinamide enantiomers, which specifically includes the following steps: a three-electrode system is adopted, with a PAA-MWCNTs-Ag-SCS complex modified electrode for chiral identification of benzylglycinamide enantiomers as a working electrode, a platinum electrode as a counter electrode, and a saturated calomel electrode as a reference electrode. The three-electrode system is immersed in a PBS solution of L-phenylglycinamide or D-phenylglycinamide for static incubation at room temperature, and then a differential pulse voltammetry curve is recorded in a 5mM potassium ferrocyanide solution of 0.1M KCl in a potential range of -0.2-0.6V.
[0014] Specifically: the concentrations of the prepared L-phenylglycinamide and D-phenylglycinamide solutions are both 10 mM, the pH of the PBS solution is 4, the concentration is 0.1 M, and the standing time is 15 min.
[0015] The invention has the following beneficial effects: the PAA-MWCNTs-Ag-SCS chiral platform has high sensitivity, strong stability and high electron conduction efficiency. The functionalized carbon nanoframework greatly improves the electron transmission performance of the chiral platform, and the silver ammonium ion functionalized chitosan forms a chiral layer on the carbon nanotube, which greatly improves the stability and chiral recognition effect of the chiral platform. The prepared chiral platform can realize the efficient and sensitive recognition of the enantiomers of phenylglycinamide. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Infrared spectra of MWCNTs, PAA-MWCNTs, CS, Ag-SCS and PAA-MWCNTs-Ag-SCS composite.
[0017] Figure 2 SEM images of MWCNTs (A), PAA-MWCNTs (B) and PAA-MWCNTs-Ag-SCS (C).
[0018] Figure 3 Cyclic voltammograms of bare glass, MWCNTs, PAA-MWCNTs, and PAA-MWCNTs-Ag-SCS composite modified electrodes used for chiral recognition of phenylglycinamide enantiomers in Example 1.
[0019] Figure 4 Impedance diagrams of bare glass, MWCNTs, PAA-MWCNTs, and PAA-MWCNTs-Ag-SCS composite modified electrodes used for chiral recognition of phenylglycinamide enantiomers in Example 1.
[0020] Figure 5 This is the differential pulse voltammogram of the PAA-MWCNTs-Ag-SCS composite modified electrode used for chiral recognition of phenylglycinamide enantiomers in Example 1.
[0021] Figure 6 This is the differential pulse voltammetry curve of the PAA-MWCNTs-Ag-SCS composite modified electrode at different ratios of PAA-MWCNTs and SCS in Example 2.
[0022] Figure 7 This is a curve diagram of 100 cycles of cyclic voltammetry scanning of the PAA-MWCNTs-Ag-SCS composite modified electrode in Example 3. DETAILED DESCRIPTION
[0023] The present invention will now be further described in conjunction with specific embodiments. The following embodiments are intended to illustrate the present invention rather than to further limit the present invention.
[0024] The present invention uses a PAA-MWCNTs-Ag-SCS composite modified electrode to identify the phenylglycinamide enantiomers according to the following method:
[0025] R D / L =I D / I L
[0026] △E=E D -E L
[0027] In the formula, R D / L represents the oxidation peak current ratio of benzyl glycinamide enantiomers, △E represents the oxidation peak potential difference of benzyl glycinamide enantiomers, I L and I D represent the oxidation peak currents of L-phenylglycinamide and D-phenylglycinamide, E L and E D Represent the oxidation peak potentials of L-phenylglycinamide and D-phenylglycinamide, respectively.
[0028] Example 1
[0029] (1) Preparation of PAA-MWCNTs: 0.1 g of multi-walled carbon nanotubes (MWCNTs) and 1 g of acrylic acid were weighed and dispersed in 100 ml of acetone by ultrasonication, and then 0.03 g of 2,2′-azoisobutyronitrile was added to initiate polymerization. The reaction was maintained at 60° C. for 12 h. The black solid product (PAA-MWCNTs) was filtered, washed with acetone and deionized water, and dried in a vacuum oven at 70° C. to obtain PAA-MWCNTs solid powder.
[0030] (2) Preparation of SCS: 1 g of chitosan (CS) was completely dissolved in 80 ml of wt% acetic acid aqueous solution. Then, under a nitrogen atmosphere, 2 g of 1,3-propane sultone salt was dropped into the CS solution and stirred at 60°C for 6 h. The solute was then poured into cold acetone and stirred vigorously to precipitate a white product. The product was completely washed with methanol to remove unreacted 1,3-propane sultone. The solid was dried in an oven for 12 h to obtain a white powder SCS.
[0031] (3) Preparation of PAA-MWCNTs-Ag-SCS suspension: 3 mg Ag 2 O solid was dissolved in 3 ml of 12.5% ammonia water, 3 mg of SCS was added, and after ultrasonication for 1 h, 3 mg of PAA-MWCNTs was added to obtain a PAA-MWCNTs-Ag-SCS suspension.
[0032] (4) Preparation of modified electrodes: 5 μL of MWCNTs, PAA-MWCNTs, and PAA-MWCNTs-Ag-SCS suspensions were respectively applied to the electrode surface and dried under an infrared lamp to obtain MWCNTs, PAA-MWCNTs, and PAA-MWCNTs-Ag-SCS composite modified electrodes.
[0033] Cyclic voltammetry test: A three-electrode system was used, with bare glass and MWCNTs, PAA-MWCNTs, and PAA-MWCNTs-Ag-SCS composite modified electrodes as working electrodes, a platinum electrode as a counter electrode, and a saturated calomel electrode as a reference electrode. The three-electrode system was immersed in a 5 mM potassium ferrocyanide solution containing 0.1 M KCl at room temperature and the cyclic voltammetry curve was recorded in the potential range of -0.2-0.6 V.
[0034] The number of cyclic voltammetric scans of the modified electrode in the supporting electrolyte is 8. Figure 3 .
[0035] Prepare MWCNTs, PAA-MWCNTs, and PAA-MWCNTs-Ag-SCS composite modified electrodes according to step (4).
[0036] Impedance test: A three-electrode system was used, with bare glass and MWCNTs, PAA-MWCNTs, and PAA-MWCNTs-Ag-SCS composite modified electrodes as working electrodes, a platinum electrode as a counter electrode, and a saturated calomel electrode as a reference electrode. The three-electrode system was immersed in a 5 mM potassium ferrocyanide solution containing 0.1 M KCl at room temperature for impedance testing. The frequency range of EIS was 10 -2 -10 -5 Hz. See Figure 4 .
[0037] Prepare the electrode modified with PAA-MWCNTs-Ag-SCS composite according to step (4)
[0038] Electrochemical identification of benzylglycinamide enantiomers: A three-electrode system was used, with a PAA-MWCNTs-Ag-SCS composite modified electrode as the working electrode, a platinum electrode as the counter electrode, and a saturated calomel electrode as the reference electrode. The three-electrode system was immersed in a PBS solution of L-phenylglycinamide or D-phenylglycinamide for static incubation at room temperature, and then the differential pulse voltammetry curve was recorded in a 5 mM potassium ferrocyanide solution containing 0.1 M KCl in the potential range of -0.2-0.6 V.
[0039] Specifically: the concentrations of the prepared L-phenylglycinamide and D-phenylglycinamide solutions are both 10 mM, the pH of the PBS solution is 4, the concentration is 0.1 M, and the standing time is 15 min. Figure 5 .
[0040] Embodiment 2:
[0041] (1) The same as step (1) in implementation 1, specifically, PAA-MWCNTs were prepared: 0.1 g of multi-walled carbon nanotubes (MWCNTs) and 1 g of acrylic acid were weighed and dispersed in 100 ml of acetone by ultrasonication, and then 0.03 g of 2,2′-azoisobutyronitrile was added to initiate polymerization. The reaction was maintained at 60° C. for 12 h, and then the black solid product (PAA-MWCNTs) was filtered, washed with acetone and deionized water, and dried in a vacuum drying oven at 70° C. to obtain PAA-MWCNTs solid powder.
[0042] (2) The same as step (2) in implementation 1, specifically, SCS was prepared: 1 g of chitosan (CS) was completely dissolved in 80 ml of wt% acetic acid aqueous solution, and then 2 g of 1,3-propane sultone salt was dropped into the CS solution under a nitrogen atmosphere, and stirred at 60° C. for 6 h. The solute was then poured into cold acetone and stirred vigorously to precipitate a white product, which was completely washed with methanol to remove unreacted 1,3-propane sultone. The solid was dried in an oven for 12 h to obtain a white powder SCS.
[0043] (3) Preparation of PAA-MWCNTs-Ag-SCS suspensions with different ratios: 3 mg Ag 2 O solid was dissolved in 3 ml of 12.5% ammonia water to obtain a diamine silver aqueous solution. Four more diamine silver aqueous solutions of the same specification were prepared in the same way, and 1 mg, 1 mg, 1 mg, 2 mg and 3 mg SCS were added respectively, followed by ultrasonic treatment for 1 h, and then 3 mg, 2 mg, 1 mg, 1 mg and 1 mg PAA-MWCNTs were added respectively to obtain PAA-MWCNTs-Ag-SCS suspensions with PAA-MWCNTs and SCS ratios of 3:1, 2:1, 1:1, 1:2, and 1:3.
[0044] (4) Preparation of electrodes modified with PAA-MWCNTs-Ag-SCS complexes of different ratios: 5 μL of PAA-MWCNTs-Ag-SCS suspensions of five different ratios were applied to the electrode surface and dried under an infrared lamp to obtain five PAA-MWCNTs-Ag-SCS modified electrodes. Electrochemical identification of benzylglycinamide enantiomers: A three-electrode system was used, with PAA-MWCNTs-Ag-SCS complex modified electrodes of different ratios as working electrodes, a platinum electrode as a counter electrode, and a saturated calomel electrode as a reference electrode. The three-electrode system was immersed in a PBS solution of L-phenylglycinamide or D-phenylglycinamide and incubated at room temperature. Then, the differential pulse voltammetry curve was recorded in a 5 mM potassium ferrocyanide solution containing 0.1 M KCl in the potential range of -0.2-0.6 V, see Figure 6 .
[0045] Specifically: the concentrations of the prepared L-phenylglycinamide and D-phenylglycinamide solutions are both 10 mM, the pH of the PBS solution is 4, the concentration is 0.1 M, and the standing time is 15 min.
[0046] Example 3
[0047] (1) Preparation of PAA-MWCNTs: 0.1 g of multi-walled carbon nanotubes (MWCNTs) and 1 g of acrylic acid were weighed and dispersed in 100 ml of acetone by ultrasonication, and then 0.03 g of 2,2′-azoisobutyronitrile was added to initiate polymerization. The reaction was maintained at 60° C. for 12 h. The black solid product (PAA-MWCNTs) was filtered, washed with acetone and deionized water, and dried in a vacuum oven at 70° C. to obtain PAA-MWCNTs solid powder.
[0048] (2) Preparation of SCS: 1 g of chitosan (CS) was completely dissolved in 80 ml of wt% acetic acid aqueous solution. Then, under a nitrogen atmosphere, 2 g of 1,3-propane sultone salt was dropped into the CS solution and stirred at 60°C for 6 h. The solute was then poured into cold acetone and stirred vigorously to precipitate a white product. The product was completely washed with methanol to remove unreacted 1,3-propane sultone. The solid was dried in an oven for 12 h to obtain a white powder SCS.
[0049] (3) Preparation of PAA-MWCNTs-Ag-SCS suspension: 3 mg Ag 2 O solid was dissolved in 3 ml of 12.5% ammonia water, 3 mg of SCS was added, and after ultrasonication for 1 h, 3 mg of PAA-MWCNTs was added to obtain a PAA-MWCNTs-Ag-SCS suspension.
[0050] (4) Preparation of modified electrode: 5 μL of PAA-MWCNTs-Ag-SCS suspension was dropped onto the electrode surface and dried under an infrared lamp to obtain a PAA-MWCNTs-Ag-SCS composite modified electrode.
[0051] Cyclic voltammetry test: A three-electrode system was used, with the PAA-MWCNTs-Ag-SCS composite modified electrode as the working electrode, the platinum electrode as the counter electrode, and the saturated calomel electrode as the reference electrode. The three-electrode system was immersed in a 5 mM potassium ferrocyanide solution containing 0.1 M KCl at room temperature and the cyclic voltammetry curve was recorded in the potential range of -0.2-0.6 V.
[0052] Specifically: the number of cyclic voltammetry scans is 100.
[0053] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A silver-ammonia ion functionalized chitosan complex modified electrode based on a carbon nanotube skeleton, characterized in that: The invention comprises a glassy carbon electrode and a PAA-MWCNTs-Ag-SCS complex modified on the surface of the glassy carbon electrode, wherein the PAA-MWCNTs-Ag-SCS complex comprises a carbon nanotube unit PAA-MWCNTs coated with polyacrylic acid and a sulfonated chitosan unit SCS, wherein the carbon nanotube unit coated with polyacrylic acid and the sulfonated chitosan unit are connected by diamine silver ions; The mass ratio of the carbon nanotube unit coated with polyacrylic acid to the sulfonated chitosan unit is 1:3-3:
1.
2. The silver-ammonia ion functionalized chitosan complex modified electrode based on carbon nanotube skeleton according to claim 1, characterized in that: Preparation of PAA-MWCNTs: Weigh multi-walled carbon nanotubes MWCNTs and acrylic acid and disperse them in 100 ml of acetone by ultrasonication. Then add 2,2´-azoisobutyronitrile to initiate polymerization. The reaction is maintained at 60°C for 12 hours. Then the black solid product is filtered, washed with acetone and deionized water, and dried in a vacuum drying oven at 70°C.
3. The silver-ammonia ion functionalized chitosan complex modified electrode based on carbon nanotube skeleton according to claim 1, characterized in that: SCS was prepared by the following method: chitosan CS was completely dissolved in 80 ml of acetic acid aqueous solution, and then 1,3-propane sultone salt was dropped into the CS solution under nitrogen atmosphere and stirred at 60 °C for 6 h. The solute was then poured into cold acetone and stirred vigorously to precipitate a white product, which was completely washed with methanol to remove unreacted 1,3-propane sultone. The solid was dried in an oven for 12 h to obtain white powder SCS.
4. The silver-ammonia ion functionalized chitosan complex modified electrode based on carbon nanotube skeleton according to claim 1, characterized in that: The PAA-MWCNTs-Ag-SCS composite was prepared by the following method, including dissolving Ag2O solid in 3 ml of 12.5% ammonia water, adding SCS, ultrasonicating for 1 h, and then adding PAA-MWCNTs to obtain a PAA-MWCNTs-Ag-SCS suspension.
5. The silver-ammonia ion functionalized chitosan complex modified electrode based on a carbon nanotube skeleton according to claim 1, characterized in that: The electrode modified by the PAA-MWCNTs-Ag-SCS complex is prepared by the following method, including: dropping a PAA-MWCNTs-Ag-SCS suspension on the electrode surface, and drying under an infrared lamp to obtain a PAA-MWCNTs-Ag-SCS complex modified electrode.
6. The use of a silver-ammonia ion functionalized chitosan complex modified electrode based on a carbon nanotube skeleton according to any one of claims 1 to 5, characterized in that: Used for electrochemical identification of phenylglycinamide enantiomers.
7. The use of the silver-ammonia ion functionalized chitosan complex modified electrode based on the carbon nanotube skeleton according to claim 6, characterized in that: The method comprises the following steps: adopting a three-electrode system, using a PAA-MWCNTs-Ag-SCS composite modified electrode for chiral recognition of benzylglycinamide enantiomers as a working electrode, a platinum sheet electrode as a counter electrode, and a saturated calomel electrode as a reference electrode; immersing the three-electrode system in a PBS solution of L-phenylglycinamide or D-phenylglycinamide for static incubation at room temperature; and then recording a differential pulse voltammetry curve in a 5 mM potassium ferrocyanide solution of 0.1 M KCl within a potential range of -0.2 to 0.6 V.
Citation Information
Patent Citations
Preparation and application of multi-wall carbon nanotube-N-carboxymethyl chitosan chiral material
CN108017725A
Multiwalled carbon nanotubes @ polyacrylic acid @ metal organic frames (MWCNTs@PAA@MOF-5) composite material and preparation method thereof
CN104689801A
Carbon nanotube / pyrene tetracarboxylic acid / chitosan chiral material, preparation method and application
CN114045540A